Punching shear strength of high strength concrete and steel fibre reinforced concrete slabs - Chanthabouala, Khatthanam (2017)
This thesis presents new in-depth discussions and design methods for high strength concrete (HSC) and steel fibre reinforced concrete (SFRC) slabs that are subjected to punching shear. Experimental programmes of 22 full-scale slabs are presented to accompany the discussions and the new design methods proposed in this thesis. All of the 22 slab specimens were constructed with high strength concrete. Some of the advantages of using high strength concrete compared to normal strength concrete include an increase in cracking load of the slab and a reduction in deflection at service load level due to higher tensile strength and higher elastic modulus of high strength concrete. This research focuses on the investigation of the influences of two main structural parameters on the punching shear strength of a slab. The two parameters concerning this research are (1) the effect of low flexural reinforcement ratios, and (2) the influence of a new type of fibres - the double hooked end fibre. Recently, several researchers have addressed and investigated the influences of these parameters; however, more research are still needed. Therefore, the following paragraphs provide a brief summary of this thesis that includes both experimental and analytical works. First, punching shear tests of 12 high-strength concrete slabs (f’c > 95 MPa) with various flexural reinforcement ratios and column aspect ratios are presented. The dimensions of the specimens are 2.2 × 2.2 × 0.15 m and 2.7 × 2.2 × 0.15 m. The resulting slab data represent a complete set of slab specimens having low to high reinforcement ratios. The purpose of the tests is to investigate if Code equations (ACI 318, Eurocode 2) for punching shear overestimate the actual punching shear strengths of slabs that are provided with low amount of flexural reinforcement or low reinforcement ratio. Other influencing factors, such as column rectangularity ratio, concrete strength, and size (thickness) effect are also addressed. The author’s new experimental results will be combined with 355 existing published data and together they will be used to evaluate the accuracy and safety of the ACI 318-14 and Eurocode 2 methods for punching shear, as well as some methods proposed by other researchers. Second, punching shear tests of 10 steel fibre reinforced concrete (SFRC) slabs tested under punching shear loads are presented. The dimensions of the specimens are 2.2 × 2.2 × 0.15 m. The influence of high strength concrete (f’c ≥ 80 MPa) and a new type of steel fibre (the double hooked end fibre) were investigated. The fibre contents were varied from zero to 1.2% volume fraction for each set of the reinforcement ratio ρ. The reinforcement ratio ρ was varied from ρ = 0.9% to ρ = 1.4%. Key attributes, such as: ultimate state and serviceability performances, of these high strength SFRC slabs are discussed. The experimental results highlight that high strength SFRC enhances the slab performance in many aspects. As the fibre volume Vf was increased from 0% to 1.2% or to an equivalent fibre dosage of 93.6 kg/m3, the flexural stiffness of the slabs increased while both the deflections and crack widths reduced. At the ultimate state, the punching shear strength increased by up to 156% compared to non-fibrous concrete slabs, which is significantly higher than the increment introduced by conventional single hooked-end fibres; the ductility and energy absorption capacity of the slabs were also significantly improved. Comparisons of design methods with the experimental results show that the TR34 method by the Concrete Society performs very well while the yield line theory overestimates the strengths of the slabs. The Model Code 2010 method is unconservative. Finally, some relevant design recommendations are given. New design methods are proposed, they will be shown to be very reliable and accurate for calculating the punching shear strength of both reinforced concrete and steel fibre reinforced concrete slabs.